2018
DOI: 10.3748/wjg.v24.i3.323
|View full text |Cite
|
Sign up to set email alerts
|

circRNA_0046366 inhibits hepatocellular steatosis by normalization of PPAR signaling

Abstract: AIMTo investigate micro (mi)R-34a-antagonizing circular (circ)RNA that underlies hepatocellular steatosis.METHODSThe effect of circRNA on miR-34a was recognized by the miRNA response element (MRE), and validated by the dual-luciferase reporter assay. Its association with hepatocellular steatosis was investigated in HepG2-based hepatocellular steatosis induced by free fatty acids (FFAs; 2:1 oleate:palmitate) stimulation. After normalization of the steatosis-related circRNA by expression vector, analysis of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 59 publications
4
58
0
Order By: Relevance
“…PPARα downregulation decreased PPARα-mediated lipid metabolism and led to hepatocellular steatosis, which indicated that circRNA_0046367/miR-34a/PPARα axis might be involved in lipoxidative and reduce hepatic steatosis-inducing HCC ( 96 ). Moreover, other same results have been observed in circRNA_0046366 ( 118 ).…”
Section: Circrnas In Hepatocellular Carcinoma (Hcc)supporting
confidence: 82%
“…PPARα downregulation decreased PPARα-mediated lipid metabolism and led to hepatocellular steatosis, which indicated that circRNA_0046367/miR-34a/PPARα axis might be involved in lipoxidative and reduce hepatic steatosis-inducing HCC ( 96 ). Moreover, other same results have been observed in circRNA_0046366 ( 118 ).…”
Section: Circrnas In Hepatocellular Carcinoma (Hcc)supporting
confidence: 82%
“…4, 5). Although several recent studies have reported that circRNAs play an important role in the stage of simple steatosis 9,32,33 , it is the first time the current study demonstrates that circRNA participates in the progression of NASH and circRNA_002581 may serve as a novel therapeutic target for the treatment of NASH.…”
Section: Discussionmentioning
confidence: 69%
“…circRNA_0046366 antagonizes miR-34a and normalizes PPARα signaling, leading to the amelioration of liver steatosis in a murine model[ 116 ]. However, a phase I study on the effects of a miR-34 mimic (MRX34) on primary liver cancer and advanced or metastatic cancer with liver involvement (ClinicalTrials.gov Identifier: NCT01829971) was prematurely terminated due to serious immune-related adverse events[ 108 ], highlighting the potential risks of miRNA based-therapies.…”
Section: Role Of Mirnas In Nafldmentioning
confidence: 99%